2004
DOI: 10.1002/cne.20056
|View full text |Cite
|
Sign up to set email alerts
|

Tectal mosaic: Organization of the descending tectal projections in comparison to the ascending tectofugal pathway in the pigeon

Abstract: The optic tectum of vertebrates is an essential relay station for visuomotor behavior and is characterized by a set of connections that comprises topographically ordered input from the eyes and an output that reaches premotor hindbrain regions. In the avian tectofugal system, different ascending cell classes have recently been identified based on their dendritic and axonal projection patterns, although comparable information about the descending cells is missing. By means of retrograde tracing, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 67 publications
1
72
2
Order By: Relevance
“…Injections into all these target layers could be verified by labeling of other efferent and afferent tectal connections. i) Tracer application within layer 13 was confirmed by bilateral fiber staining within the nucleus rotundus (Hellmann and Güntürkün, 1999), within the mainly contralaterally descending tectobulbar as well as the mainly ipsilaterally projecting tectopetal fiber tracts (Hellmann et al, 2004). ii) Tracer application into the superficial laminae was confirmed by labeled cells located within Ipc which projects onto layers 2-13 (Wang et al, 2006), Imc (nucleus isthmi magnocellularis) which terminates in layers 10 -12 (Wang et al, 2004), Slu which project onto the layers 4 -13 Wang et al, 2006), PT (nucleus pretectalis) which projects onto layer 5 (Gamlin et al, 1996), and VLT (nucleus ventrolateralis thalami) which projects onto layers 11-14 (Hunt and Brecha, 1984;Schulte et al, 2006).…”
Section: Quantitative Differences Between Left and Right Tectal Injecmentioning
confidence: 90%
“…Injections into all these target layers could be verified by labeling of other efferent and afferent tectal connections. i) Tracer application within layer 13 was confirmed by bilateral fiber staining within the nucleus rotundus (Hellmann and Güntürkün, 1999), within the mainly contralaterally descending tectobulbar as well as the mainly ipsilaterally projecting tectopetal fiber tracts (Hellmann et al, 2004). ii) Tracer application into the superficial laminae was confirmed by labeled cells located within Ipc which projects onto layers 2-13 (Wang et al, 2006), Imc (nucleus isthmi magnocellularis) which terminates in layers 10 -12 (Wang et al, 2004), Slu which project onto the layers 4 -13 Wang et al, 2006), PT (nucleus pretectalis) which projects onto layer 5 (Gamlin et al, 1996), and VLT (nucleus ventrolateralis thalami) which projects onto layers 11-14 (Hunt and Brecha, 1984;Schulte et al, 2006).…”
Section: Quantitative Differences Between Left and Right Tectal Injecmentioning
confidence: 90%
“…This visual input arises from not only the tectofugal system, via the pontine nuclei, but also the nucleus lentiformis mesencephali (LM) of the pretectum [Pakan et al, 2005;Pakan and Wylie, in press]. Although the tecto-pontine system is involved in processing local motion [e.g., Frost and Nakayama, 1983] for orientation and avoidance [Ewert, 1970;Ingle, 1970;Hellmann et al, 2004], the LM processes 'optic flow' and is important for generating optomotor responses [e.g., Gioanni et al, 1983;Winterson and Brauth, 1985;McKenna and Wallman, 1985;Wylie and Crowder, 2000]. It has been suggested that an integration of local motion analysis and optic flow analysis is important for 'steering behaviour' during locomotion in complex environments [Sherk and Fowler, 2001;Elder et al, 2005;Page and Duffy, 2005;Sato et al, 2005;Logan and Duffy, in press].…”
Section: Behavioral Correlates Of Folium Sizementioning
confidence: 99%
“…Dendritic arborizations could not be detected higher than up to layer 12. Thus, this deep population resembles cells of the descending tectal output [20]. Moreover, massive labeling of multipolar cells was observed mainly in the ventral part of the ipsilateral nucleus isthmi, pars semilunaris (SLu, A 1.75-A 2.25; Fig.…”
Section: Analysis Of Ctb Injectionsmentioning
confidence: 79%
“…5). These deep tectal laminae are in part the source of the diverse descending tectomotor output pathways [20]. Since VLT neurons are partly GABAergic [9], this diencephalic structure could inhibit some tectal circuits while activating others.…”
Section: Afferents Of Vltmentioning
confidence: 99%